1997
DOI: 10.1148/radiographics.17.3.9153698
|View full text |Cite
|
Sign up to set email alerts
|

Takayasu arteritis: protean radiologic manifestations and diagnosis.

Abstract: Diagnosis of Takayasu arteritis is difficult because the clinical features are similar to those of other diseases. In early-phase Takayasu arteritis, computed tomography (CT) and magnetic resonance (MR) imaging show thickening of the aortic wall. Late-phase Takayasu arteritis has been classified into four types: classic pulseless disease (type I), a mixed type (type II), the atypical coarctation type (type III), and the dilated type (type IV). In late-phase Takayasu arteritis, angiography usually demonstrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0
12

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(96 citation statements)
references
References 0 publications
2
82
0
12
Order By: Relevance
“…Doppler ultrasonography, CT and MRI are important tools in diagnosis, but there is no specific imaging technique or serum biomarker. Although conventional angiography is the standard imaging technique in TA [7]. Recent studies demonstrated that 18F-FDG PET/CT can be helpful in assessment of disease activity before treatment as well as to monitor therapeutic effect or to detect relapse of the disease despite the therapy [8].…”
Section: Discussionmentioning
confidence: 99%
“…Doppler ultrasonography, CT and MRI are important tools in diagnosis, but there is no specific imaging technique or serum biomarker. Although conventional angiography is the standard imaging technique in TA [7]. Recent studies demonstrated that 18F-FDG PET/CT can be helpful in assessment of disease activity before treatment as well as to monitor therapeutic effect or to detect relapse of the disease despite the therapy [8].…”
Section: Discussionmentioning
confidence: 99%
“…Although studies on Takayasu's arteritis concerning early diagnosis or evaluation of corticosteroid therapy by MRimaging or angiography have been sporadically performed (8)(9)(10), recent advances in diagnostic imaging technology have enabled MRangiography of a STA with a very small diameter to be performed (1 1 , 12). We have evaluated visualization of the STA by MRangiography in other patients or in healthy volunteers and have confirmed that the vessel can be visualized in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting variable ischemic symptoms secondary to arterial stenosis, occlusion, or arterial dilatation and aneurysmal formation cause various clinical conditions, such as arm claudication, decreased arterial pulses, carotodynia, visual loss, stroke, aortic regurgitation and arterial hypertension 30 . Topological classification of Takayasu's arteritis is based on the vascular provinces that are affected 31 , with either affection of the branches of the aortic arch (Type I), the ascending aorta, aortic arch and its branches (Type IIa), the ascending aorta, aortic arch and its branches and the thoracic descending aorta (Type IIb), the thoracic descending aorta, abdominal aorta, and/or renal arteries (Type III), the abdominal aorta and/or renal arteries (Type IV) or combined features of types IIb and IV.…”
Section: Takayasu's Arteritismentioning
confidence: 99%